Empaglifozin mitigates NAFLD in high-fat-fed mice by alleviating insulin resistance, lipogenesis and ER stress - Petito-da-Silva, Tamiris Ingrid; Souza-Mello, Vanessa; Barbosa-da-Silva, Sandra (Molecular and cellular endocrinology, 2019)
To evaluate the pleiotropic effects of empagliflozin in the liver through lipogenesis, beta-oxidation, and endoplasmic reticulum stress pathways. Male C57Bl/6 mice, 3 months of age, received a control diet (C, 10% lipids, n = 20) or high-fat diet (HF, 50% lipids, n = 20) for 10 weeks, after that, the groups were subdivided to receive empagliflozin, during 5 weeks at a dose of 10 mg/kg/day added to the diets, totalizing four groups: C, C-EMPA, HF, and HF-EMPA. We performed biochemical analyzes, oral glucose tolerance test, homeostasis model assessment of insulin resistance (HOMA-IR), indirect calorimetry, liver stereology, western blotting, RT-qPCR for genes related to beta-oxidation, lipogenesis, and endoplasmic reticulum stress. After the treatment with empagliflozin, there was a 4% increase in energy expenditure, a 5% reduction in body mass, improvement in glucose tolerance and insulin sensitivity and insulin resistance. The expression of Ppar alpha was greater in the HF-EMPA group with a concomitant reduction in the expression of the lipogenic genes Fas, Srebp1c and Ppar gamma, according to protein expression. In addition, HF-EMPA showed a reduction in the genes related to endoplasmic reticulum stress Chop, Atf4, and Gadd45. Empagliflozin mitigates the development of NAFLD, confirmed through reduced expression of the genes involved in hepatic lipogenesis and genes involved in endoplasmic reticulum stress. Thus, empagliflozin may be an important tool to treat the progression of hepatic steatosis. NAFLD is associated with increase in lipogenic and inflammation pathways imbalance, with detrimental for beta-oxidation and reticulum endoplasmic function. On the other hand, empagliflozin treatment ameliorates hepatic steatosis through lipogenic pathway reduction, beta-oxidation augmentation and attenuation of endoplasmic reticulum stress and consequently inflammation markers reduction, in high fat fed C57Bl/6 mice. [Display omitted] •Empagliflozin reduces body mass by increasing energy expenditure through the AMPK pathway.•Hepatic steatosis is reduced with empagliflozin by reducing hepatic lipogenesis.•Empagliflozin attenuates hepatic endoplasmic reticulum stress through eIF2-alpha, ATF4-CHOP.